List Making in the Home - Taylor, Alex; Swan, Laurel (Association for Computing Machinery, Inc., 2004)
This paper presents research on the use of household lists. Drawing on an ethnographic study of mothers’ work, it focuses on the centrality of paper lists in home- and child-care arrangements, and reveals that they provide a useful means for organizing the complex interrelations between a household’s people, activities and tasks. However, paper lists are also shown to be poor at handling the separation, or classification, of these things. In conclusion, both these positive and negative aspects of list making are used to raise broad pointers for CSCW and system design.